A Novel Signature of 23 Immunity-Related Gene Pairs Is Prognostic of Cutaneous Melanoma - Xue, Ya-Nan; Xue, Yi-Nan; Wang, Zheng-Cai; Mo, Yong-Zhen; Wang, Pin-Yan; Tan, Wei-Qiang (Frontiers in Immunology, 2020)
In this study, we aimed to identify an immune-related signature for predicting prognosis in cutaneous melanoma (CM). Sample data from The Cancer Genome Atlas (TCGA; n = 460) were used to develop a prognostic signature with 23 immune-related gene pairs (23 IRGPs) for CM. Patients were divided into high- and low-risk groups using the TCGA and validation datasets GSE65904 (n = 214), GSE59455 (n = 141), and GSE22153 (n = 79). The ability of the 23-IRGP signature to predict CM was precise, with the stratified high-risk groups showing a poor prognosis, and it had a significant predictive power when used for immune microenvironment and biological analyses. We subsequently established a novel promising prognostic model in CM to determine the association between the immune microenvironment and CM patient results. This approach may be used to discover signatures in other diseases while avoiding the technical biases associated with other platforms.